Partai Politik dan Keterwakilan Perempuan (Analisis Problematika Partai Politik dalam Memenuhi Keterwakilan Perempuan di DPRD) - ana sabhana azmy; Isnaini Anis Farhah (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2018)
Abstract.This research investigates the problems of political parties in meeting the quota of women’s representation in Parliament of Lebak Regency for the period 2014-2019. The objectives of this research are to know the importance of women’s representation and to analyze the barriers that caused difficulties for political parties to fulfill women’s representation in Parliament of Lebak Regency for the period 2014-2019. Method that used in this research is qualitative research with documentation and interview as the data collection technique. Theories used in this research are political party theories by Larry Diamond and women's representation by Anne Phillips and Nadezhda Shvedova. The research found two findings. First, women’s representation in Parliament of Lebak Regency is strongly important. Due to the presence of women in Parliament of Lebak Regency can bring women’s interests in politics. Second, the importance of women’s representation in Parliament of Lebak Regency is not supported by a quota of women’s representation in Parliament of Lebak Regency at which only 14%. There are three barriers that caused difficulties for political parties to fulfill women’s representation quota in Parliament of Lebak Regency for the period 2014-2019, namely political barriers, socio-economics barriers, and ideological and psychological barriers. Abstrak. Penelitian ini membahas tentang problematika partai politik dalam memenuhi kuota keterwakilan perempuan di DPRD Kabupaten Lebak periode 2014-2019. Tujuan penelitian ini adalah untuk mengetahui pentingnya representasi keterwakilan perempuan dan menganalisis kendala-kendala yang menyebabkan partai politik sulit memenuhi keterwakilan perempuan di DPRD Kabupaten Lebak periode 2014-2019. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan teknik pengumpulan data yaitu studi dokumentasi dan wawancara. Teori yang digunakan adalah teori partai politik dari Larry Diamond dan teori keterwakilan perempuan dari Anne Philips dan Nadezhda Svedova. Hasil penelitian menunjukkan bahwa, pertama, representasi keterwakilan perempuan di DPRD Kabupaten Lebak sangat penting. Hal ini karena dengan hadirnya perempuan di DPRD Kabupaten Lebak dapat membawa kepentingan-kepentingan perempuan dalam politik. Kedua, pentingnya representasi perempuan di DPRD Kabupaten Lebak tidak didukung dengan kuota keterwakilan perempuan di DPRD Kabupaten Lebak yakni hanya 14%. Ada tiga kendala yang menyebabkan partai politik sulit untuk memenuhi kuota keterwakilan perempuan di DPRD Kabupaten Lebak periode 2014-2019 yaitu kendala politik, kendala sosio-ekonomi, serta kendala ideologis dan psikologis.